Functional gynodioecy in Opuntia quimilo (Cactaceae), a tree cactus pollinated by bees and hummingbirds - Díaz, Lucrecia (2003)
The tree cactus Opuntia quimilo is one of three known gynodioecious cacti. Its flowers deviate from most Opuntias in features that are attributable to ornithophily: petals are shiny red in colour, and fleshy in consistency, a nectar chamber is present, and stamen seismonasty is lacking. Pollinators include large matinal bees (predominantly Ptilothrix tricolor and Megachile sp.) and hummingbirds (Chlorostilbon aureoventris and Heliomaster furcifer). Hummingbirds rarely visit other local Opuntias. Hummingbirds, which are more common in the afternoon, prefer female flowers whereas bees prefer hermaphroditic flowers. Female flowers have more dilute nectar than hermaphroditic flowers. Under experimental conditions female fertility is as high as that of hermaphrodites, however, seeds from females always result from cross‐pollination and from more severe ovule selection (ovule number is higher in female flowers). Under natural conditions female plants are reproductively more successful than hermaphrodites. Known cases of bird pollination in Opuntia and the incidence of ornithophilic features in Opuntia and related genera are discussed.